Off-shell unimodular N = 1, d = 4 supergravity - Jesus Anero; Carmelo P. Martin; Raquel Santos-Garcia (Journal of High Energy Physics)
Abstract We formulate a unimodular N = 1, d = 4 supergravity theory off shell. We see that the infinitesimal Grassmann parameters defining the unimodular supergravity trans- formations are constrained and show that the conmutator of two infinitesinal unimodular supergravity transformations closes on transverse diffeomorphisms, Lorentz transforma- tions and unimodular supergravity transformations. Along the way, we also show that the linearized theory is a supersymmetric theory of gravitons and gravitinos. We see that de Sitter and anti-de Sitter spacetimes are non-supersymmetric vacua of our unimodular supergravity theory.